Optimasi Pencahayaan Alami pada Masjid Konsep Terbuka di Samarinda - Bhanu Rizfa Hakim; Ayu Asvitasari; Feliksdinata Pangasih (Universitas Sebelas Maret Surakarta, 2024)
The mosque serves as a place of worship for the Muslim community and is imperative to possess an optimal level of comfort. Mosque design has evolved not only in terms of functionality but also in considering the comfort level through the utilization of natural lighting. The utilization of Natural Lighting emerges as a significant choice, particularly for mosques with expansive areas, facilitating energy conservation. Challenges in implementing natural lighting in mosque design, especially in open concepts, include temperature rise and glare effects that may disrupt worship comfort. Research methodology involves measuring the incoming light values using a lux meter and conducting thermal envelope measurements using a thermal camera (FLIR) within the spaces of the open-concept mosque, followed by simulation to devise a design for sunshade fins. The design of sunshade fins aids in temperature reduction while maintaining natural light penetration and mitigating glare issues in open-concept mosques.